Mamíferos do cerrado de Mato Grosso, com ênfase no uso do espaço por Cerdocyon thous (Carnivora, Canidae) e Mazama gouazoubira (Artyodctyla, Cervidae) - Santos Júnior, Tarcísio da Silva (2005)
This research was developed in the Cerrado environments located in the municipalities of Chapada dos Guimarães (MT) and Rosario Oeste (MT), to study the abundance of Terrestrial Mammals of Medium and Large Size as well as the use of space by crab-eating fox, Cerdocyon thous, and the gray brocket deer, Mazama gouazoubira. It was conducted between 2000 and 2004 in four areas: reservoir of Manso hydroelectric powerplant (APM-Manso: 14°52'15" S, 55°47'5"W), Chapada dos Guimarães National Park (PARNA-CG: 15°24'13"S, 55°49'50"W), Comunidade São Jerônimo (CSJ: 15°25'40"S, 55°53'54"W) and Panflora farm (Panflora: 15°4'43"S, 56°33'15"W). Line transects were sampled by car in order to study abundance of mammals. The effort of covering 1560 km allowed registering 14 out of the 21 species expected to occur in the region. The C. thous was the most abundant in all areas, followed by M. gouazoubira, which in turn was less abundant than the pampas deer, Ozotoceros bezoarticus in PARNACG. The results showed differential density of species between the sites surveyed. The study of the use of space by C. thous and M. gouzoubira was performed by equipping adults with conventional biotelemetry radiotransmiters. Research on C. thous was developed in the APM-Manso and Panflora to study the size and overlap of its home range and survival. The species M. gouazoubira was monitored only in the APM Manso with the aim of studying relocated individuals concerning their survival, the displacement pattern in post- releasing, along with the size and overlap of home range. The size of the home range of C. thous of APM Manso ranged from 128 to 1441 ha and whereas Panflora ranged from 20 to 1235 ha. In both sites, home range overlap was practically restricted to pairs of males and females. The deaths of the animals tracked were caused by running over and natural predation, resulting in survival of 26 % in the APMManso and 50 % in Panflora. Of the 19 individuals of M. gouazoubira rescued in APM-Manso, 14 were equipped with transmitters and tracked. The survival was of 60 % and the average distance covered was 11.4 km from the releasing site. The average time to establish home range was 45.6 days, their average size of 111.3 ha and there was no record of overlapping among them.